Desenvolvimento de barras alimentícias e biscoitos isentos de glúten, contendo chenopodium quinoa, BRS Piabiru, Amaranthus cruentus, BRS Alegria e Linum usitiasimum, L - Pagamunici, Lilian Maria (2013)
Celiac disease (CD) is the intolerance to gluten protein, which presents stance to the digestive enzymes and triggers an inflammatory response in genetically predisposed individuals. The main treatment is based on restricting the consumption of foods containing this protein fraction. Food containing gluten, such as oats, barley, rye and wheat, causes inflammation in the intestinal villi, followed by atrophy and low absorption of nutrients in affected individuals. CD is one of the most frequent genetic diseases of humanity, affecting 0.5% lo 1.0% of world population. In Brazil, studies performed in blood banks screening, indicate the prevalence of CD in 1:276 to 1:681 of donors. Most of industrial products have gluten in their composition, making the diet of patients with this disease very difficult, which becomes monotonous and restricted. Besides, these products usually have high amounts of simple carbohydrates and saturated fats. The development of food for celiac patients with good nutritional contribution corresponds to the needs of this class of consumers. Rice flour is an alternative to replace wheat flour in bakery products processing such as gluten free cookie, because it does not contam this protein fraction, but the amino acid profile is deficient in lysine. In most cereal bars available in the market, the main ingredient is oats and contents of saturated fat are high in these bars. An alternative for the production of cookies and food bars for celiac with good nutritional support is the use of gluten-free ingredients with essential nutrients. In this context, quinoa, amaranth and flaxseed are emphasized. Quinoa and arnaranth are pseudocereals (grains with similar proximate composition of cereals) originated from Andean regions, mainly from Chile. The grains are highlighted due to high quality proteins and mineral composition. Amaranth presents approximately 12-13% protein, 67-69% carbohydrates, 10-13% fiber, 5-6% fat and 2-3% minerais. Quinoa has 14-15% protein, 55-64% carbohydrates, 9-11% fiber, 6-10% fat and 3- 4% minerals. The constitution of these two pseudocereals also presents saponins, which act as natural antimicrobial agent and insecticide for the plant, but in high concentrations in the human body they become toxic. In order to adapt crops of quinoa and amaranth to the Brazilian climate for cuitivation of the species in the country, the Brazilian Agricultural Research Corporation (EMBRAPA) developed crops of quinoa and amaranth, genetically modified, resulting in the species Chenopodiuin quinoa BRS Piabiru and Amaranthus cruentus BRS Alegria without saponins. Flaxseed stands out for its high content of Omega-3, considerate as an alternative to improve the lipid profile of gluten-free products because the grain has 14-22% oleic acid, 15-17% linoleic acid and 52-60% alpha-linolenic acid in relation (o its total lipids (44%). Therefore, the development of products ready for consumption such as gluten free cookie and food bar, with good nutritional finds the needs of the celiac consuming public. Besides the nutritional composition, another topic to be taken into consideration in the development of food bars and cookies is sensory acceptance. The influence of ingredients on the sensory, nutritional and technological characteristics can be detected with the use of chemometric tools, because they allow the recognition of patterns, Information gathering and a reduction of data dimensionality, as well as the organization of them in a more simple and easy to understand structure. The principal component analysis is based on achievement and linear comparisons of the original variables. The principal components (PCs) are mutually orthogonal and expIain the decrease in variance with increase in number of PCs... cont.